2021
DOI: 10.21037/atm-21-1226
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the modified sinus tarsi approach versus the extensile lateral approach for displaced intra-articular calcaneal fractures

Abstract: Background: This study sought to assess and compare the clinical efficacy and complications of a modified sinus tarsi approach (MSTA) and the extensile lateral approach (ELA) in the treatment of displaced intraarticular calcaneal fractures. Methods: This retrospective study enrolled 108 patients (117 feet) with Sanders II-IV calcaneal fractures, including 52 patients (56 feet) in the MSTA group and 56 patients (61 feet) in the ELA group. The functional and radiological results of the affected feet were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…A literature review examining calcaneus fractures report that there are generally more wound site problems in patient groups operated with the EL approach compared to the ST approach. Ma et al (15) found the complication rate related to wound healing to be 14.75% in the EL approach and 5.36% in the ST approach, and they reported that the difference was statistically significant. Lin et al (20) found that the wound infection rate was higher in Sanders type IV fractures, which were 34.04% in the EL approach and 14.28% in the ST approach.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…A literature review examining calcaneus fractures report that there are generally more wound site problems in patient groups operated with the EL approach compared to the ST approach. Ma et al (15) found the complication rate related to wound healing to be 14.75% in the EL approach and 5.36% in the ST approach, and they reported that the difference was statistically significant. Lin et al (20) found that the wound infection rate was higher in Sanders type IV fractures, which were 34.04% in the EL approach and 14.28% in the ST approach.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Kwon et al (27) found that postponing surgery did not reduce the wound complication rates when the EL approach was used, while the wound complication rate increased when minimally invasive approaches were used. Ma et al (15) reported that the patients in the ST group had a significantly shorter waiting time from injury to surgery than the EL group and that the wound site problem was less in the ST group. They stated that this resulted in a shorter hospital stay and lower costs in the ST group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sustentaculum tali are essential in maintaining the internal foot column, so conservative treatment may not be appropriate for displaced sustentacular fractures. Although the extensile lateral approach and tarsal sinus approach are most commonly employed for the operational treatment of calcaneal fractures [17][18][19][20] , the tarsal sinus method is gaining popularity [17][18][19][20] . One downside of this isolated lateral incision is that the sustentacular fragments cannot be managed directly, and the visualization of the sustentacular fragments is limited.…”
Section: Discussionmentioning
confidence: 99%